App-Based Volleyball Scoreboard Performance Evaluation - Santoso, Sholeh Agus; Satria, M. Haris (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This research aims to develop and evaluate an application-based volleyball scoreboard game device designed to facilitate the process of recording and managing scores in real time. Materials and methods. This research uses the R&D development method which aims to develop a device-based volleyball game scoreboard application. This research involved 3 IT experts, 5 referees who acted as evaluators of the initial product that had been developed. In addition, there were 5 samples in the small-scale test and 30 samples in the large-scale test. Results. The results of the analysis of the development of application-based volleyball scoreboard game devices by conducting feasibility / justification tests involving economic, technical, business and environmental aspects by refereeing experts, which obtained an average value of 91.60%, where the value was included in the very good category. While the results of the analysis of IT experts obtained an average value of 90.89%, where the value is included in the very good category. The results of the analysis of the effectiveness of the media development of the application-based volleyball scoreboard game device through a small scale test, which obtained an average value of 92.63%, which means it can be concluded that the development model of the application-based volleyball scoreboard game device that has been developed can be implemented/applied with a very good category. Meanwhile, the results of the large-scale test or broad-scale test obtained an average value of 90.94%, which means it can be concluded that the development model of the application-based volleyball scoreboard game device that has been developed is in the excellent category. Conclusion. In conclusion, this application-based volleyball scoreboard game device can be an effective solution to overcome the obstacles of manual score recording, while improving the quality of organising volleyball matches